Dinamika Aging Population dan Faktor Demografi terhadap Realisasi Dana Dekonsentrasi Kesehatan di Jawa - Ramadhan, Dicky Satria; Ramadhan, Eka Setya; Septianingsih, Hesti (Lingka Ekonomika, 2026)
Java Island, Indonesia’s economic hub, faces challenges from a demographic shift toward an aging society, marked by a growing elderly population. This trend raises demand for healthcare services and pressures local government finances, especially in managing health decentralization funds. This study analyzes the impact of aging on fund realization in six provinces during 2015–2024 using panel data. Results show the elderly population has a positive and significant effect, while life expectancy and total population have significant negative effects. The old-age dependency ratio is not significant. Overall, all variables influence fund realization, emphasizing the need for adaptive health policies.